UPAYA HUKUM KONSUMEN PEMAKAI JASA KATERING TERHADAP PENYEDIA JASA KATERING YANG MELAKUKAN WANPRESTASI BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Rusmini Rusmini; Juniar Hartikasari (Fakultas Hukum Universitas IBA Palembang, 2022)
ABSTRACT In the catering business agreement, default often occurs in the catering business provider, either by the provider or the consumer. The definition of Catering according to Sjahmien Moehyi is a type of food service where the place to cook food is different from the place to serve food. Defaults that are often carried out by catering business providers include delays in serving, incompatibility of the menu served with the agreed menu, and the lack of quantity of consumption that should be provided. Meanwhile, the default on the part of consumers is generally late payments or not making payments at all. The type of research that the author uses is normative legal research, which is a legal research method carried out by examining library materials or secondary data. The approach used by the researcher is a normative juridical approach which means finding the truth of coherence. Based on Article 45 paragraphs (1) and (2) of the UUPK, legal remedies that can be taken by consumers through settlement methods are carried out through the Consumer Dispute Settlement Agency (BPSK) and through the courts. This means that the settlement of consumer disputes can be determined out of court (BPSK) and through the courts.